Aromatherapy Massage with Geranium Essence for Pain Reduction of Primary Dysmenorrhea: A Double Blind Clinical Trial - Mousa Sajjadi; Narjes Bahri; Mahnaz Abavisani (Mashhad University of Medical Sciences, 2018)
Introduction: Primary dysmenorrhea is one of the most common gynecologic problems in women. Aromatherapy is one of the non-pharmacological methods in the treatment of primary dysmenorrhea. This research was performed to study the effects of aromatherapy massage with scented geranium oil on the pain intensity in primary dysmenorrhea. Methodology: This randomized clinical trial was conducted in 2017.  90 students of Neyshabour University of Medical Sciences who had primary dysmenorrhea were randomly allocated to three groups. Subjects in the intervention group were massaged with scented geranium oil 5% and in placebo group; the same procedure was performed using sweet almond oil on the symphysis pubis region for 15 minutes. The intervention and placebo groups received the massage on the first day of menstruation in two consecutive cycles. The control group received no intervention and the severity of their pain was recorded in each cycle. The pain intensity was measured before, immediately after and 24 hours after the treatment using visual analogue scale. SPSS software (version 19) was used for data analysis and p value less than 0.05 was considered significant. Findings: There was no statistically significant difference in pain intensity between three groups in the menstrual cycle before the initiation of study. There was no significant difference in pain intensity before intervention in the first and second menstrual cycle before the intervention. There was a significant difference in pain intensity between three groups immediately after and 24 hours after the intervention in the first and second menstrual cycles ( P<0/001). Pain reduction with scented geranium oil was significantly more than massage with sweet almond oil (P<0/001). Conclusion: Aromatherapy massage with geranium essence can be used as a non-pharmacological method to reduce the pain of primary dysmenorrhea.